STRATEGIC PLANNING IN INFORMATION RESOURCES MANAGEMENT - Cezar VASILESCU (Journal of Defense Resources Management, 2013)
The field of strategic management has offered a variety of frameworks and concepts for the past years, many with the declared aim of “taking business and its management seriously”. Strategic planning can help an organization to build its sustained competitive advantage in the face of an uncertain marketplace, but it requires new ways of thinking in order to create feasible alternatives. This article examines how the Chief Information Officer (CIO) can use strategy and planning as an enabler to meet the mission of an organization. The analysis focuses on some common problems that occur in strategic planning. Managers need to identify these potential issues, so that they can recognize and deal with them if they arise in their own strategic planning. A systems approach is taken which presents planning as an open inclusive process that seeks to produce flexible systems capable of growth and adaptation to meet changing needs and missions.